DAMPAK PENGUMUMAN TAX AMNESTY PADA SAHAM LQ-45 BEI - Fernando, Eduard; Suryantini, Ni Putu Santi (E-Jurnal Manajemen; Vol 7 No 1 (2018)DO - 10.24843/EJMUNUD.2018.v7.i01.p14, 2018)
This study aims to determine the impact of tax amnesty announcement by looking at differences in average abnormal return and average abnormal return generated before and after tax amnesty announcement on BEI. This study uses 45 companies listed in LQ-45 period February 2016 s / d July 2016. Data analysis technique using approach of mean adjusted model to find abnormal return, then result of data analysis tested with t-test and paired sample t-test. The results of the study found that there were varied but not statistically significant market reactions. This indicates that investors as market participants assume this announcement information does not contain meaningful information for investors, so investors in the capital market do not react. Furthermore, the test data using paired sample t-test shows that there is no significant difference between the average abnormal return obtained by all companies listed on LQ-45 shares in Indonesia Stock Exchange before and after tax amnesty announcement.